The Determinants of Individual Union Membership in Australia: A Structural Approach Using Panel Data1. Issue 1 (8th December 2017) - Dobbie, Michael; Nahm, Daehoon
Abstract : This paper uses The Household, Income and Labour Dynamics in Australia survey to estimate a structural probit model of the determinants of individual union membership. The paper finds that union membership responds positively to the wage differential between union and non‐union workers. Consistent with other Australian and overseas research, we find that job rather than individual characteristics are the most important determinants of the probability of union membership. We contrast our research with previous Australian research from the 1980s when unionism was compulsory for many workers. We find significant similarity between the major drivers of individual union membership.